Scientific problem of modifying of primary crystals a -phase of silumin castings. Solutions - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия)
It is shown that intermetallic metals of the modifying ligatures are not the crystallization centers of primary crystals of a a-phase. As the main demodifier serves hydrogen dissolved in liquid silumin. For a solution of the problem of modifying of primary crystals of a a-phase in castings from silumins it is necessary to accept a presumption that crystallization centers of primary crystals of a a-phase are the crystalline developments consisting of a-phase nanocrystals, and the role of the modifying intermetallic metals of modifiers comes down to the active absorption of the dissolved hydrogen.